(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The contribution of mindfulness and self-efficacy in improving moral judgement under artificial intelligence (AI) governance is investigated in this work. Ensuring ethical technology use calls on leaders to combine technical developments with moral responsibility as artificial intelligence systems progressively affect important decision-making. Although mindfulness is becoming more and more popular in many spheres, its effects on difficult decisions in AI governance are yet little known. This paper looks at how self-efficacy, spiritual intelligence, and mindfulness support moral reasoning, openness, and responsibility in artificial intelligence governance. Using a secondary data analysis technique, policy studies, scientific literature, and AI ethics frameworks are analysed to find important themes in ethical consciousness, self-efficacy, and responsible AI management. The results imply that mindfulness improves attention in high-stakes decision-making, helps AI professionals clearly negotiate ethical conundrums, and stimulates innovation in handling ethical AI issues. Moreover, spiritual intelligence enhances integrity while self-efficacy helps people to boldly face moral dilemmas. Including these components into organisational training courses and AI ethics education would help to greatly increase ethical AI applications. Future studies aiming at developing globally flexible AI policy suggestions should investigate cross-cultural variations in mindfulness and self-efficacy.